An integrative review of water demand management in public organisations - Tinashe Mukonavanhu; Danielle Nel-Sanders (Water Policy, 2026)
ABSTRACT Graphical abstract summarizing a study on water demand management (WDM) in public organizations, showing the research gap, methods, key findings, theory-practice gap, and proposed Water Balance Forecasting Model (WBFM) solution. This study aims to investigate empirical research results related to water demand management in the public sector, as reported in scholarly journals. Furthermore, it aims to answer the question: What are the practical challenges and opportunities associated with the implementation of effective water demand management strategies within a particular municipal setting, specifically through the case study of the Vhembe District Municipality? Research on water demand management within public sectors has predominantly focused on elements including water supply, organisational frameworks, management methodologies, and improvement strategies. The research methodology employed an integrative review in conjunction with open-ended semi-structured interviews to enable data triangulation. This approach facilitated a comparative analysis between the insights gathered from the interview research participants and the results obtained from the integrative review. The results from the interviews expose a lack of adequate planning for water demand management within Vhembe District Municipality, causing poor water resources management. The study findings point to a lack of research based on water demand management in public sectors, specifically regarding the use of empirical methods and data. The current study analyses these results and offers a new framework towards propagating effective water demand management in government sectors.